2014
DOI: 10.3390/rs6021275
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Two Standard MODIS Satellite Burned-Area Products and an Empirically-Derived Merged Product in South Africa

Abstract: Abstract:The 500-m Moderate Resolution Imaging Spectroradiometer (MODIS) burned area products, MCD45A1, MCD64A1, and a merged product were validated across six study sites in South Africa using independently-derived Landsat burned-area reference data during the fire season of 2007. The objectives of this study were to: (i) investigate the likelihood of the improved detection of small burns through an empirically-derived merged product; (ii) quantify the probability of detection by each product using sub-pixel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 43 publications
5
35
0
2
Order By: Relevance
“…Regardless of the algorithmic strategy used to tell burned and non-burned pixels apart, all methods are normally designed to be as accurate as possible; that it to say, to obtain low commission errors, even if that means omitting a larger number of burned pixels [39,79]. In this respect, results of this study are in agreement with most previous published works using MODIS data for various regions and ecosystems [33,34,39,58,[80][81][82][83][84][85][86][87][88]. However, a great variability was found in Burned Area percentages detected by the products under consideration for the various fires (Tables 5 and 6).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Regardless of the algorithmic strategy used to tell burned and non-burned pixels apart, all methods are normally designed to be as accurate as possible; that it to say, to obtain low commission errors, even if that means omitting a larger number of burned pixels [39,79]. In this respect, results of this study are in agreement with most previous published works using MODIS data for various regions and ecosystems [33,34,39,58,[80][81][82][83][84][85][86][87][88]. However, a great variability was found in Burned Area percentages detected by the products under consideration for the various fires (Tables 5 and 6).…”
Section: Discussionsupporting
confidence: 82%
“…This product failed to identify a single pixel as burned in the five fires with fewer than 400 ha. Similar findings were reported by Tsela et al [82], who suggested the combination of the two MODIS BA products (MCD45A1 and MCD64A1) would improve detection of small burned scars in South Africa. Fornacca et al [34] also report the worse performance of MCD64A1 in the detection of small burned areas in the mountainous region of Yunnan (China) in the years 2006 and 2009, compared to the product that does not use active fires (MCD45A1).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The images already have atmospheric corrections for gases, thin cirrus clouds and aerosols [55]. The MODIS data is increasingly used to monitor burned areas and active fire over large geographic areas (e.g., [56][57][58][59][60][61][62][63]). The study area is contained in just one MODIS scene (tile h13v10).…”
Section: Modis/terra Time-series Datamentioning
confidence: 99%
“…Today, global-long term systematic-mapping of burned areas are provided by MODIS MOD45 and MOD64 products [19]. These products have been validated globally [20] and regionally by different research groups [21][22][23][24]. However, the performance of these algorithms for mapping sub-canopy burning, particularly in tropical regions, is deficient in accurately detecting the timing and extent of understory forest fires.…”
Section: Sampling Design Rationalementioning
confidence: 99%